Effects of CO2 Aeration and Light Supply on the Growth and Lipid Production of a Locally Isolated Microalga, Chlorella variabilis RSM09 - Aiya Chantarasiri; Sunisa Ungwiwatkul (Applied Sciences)
The Chlorophyceae algae, specifically Chlorella spp., have been extensively researched for biodiesel production. This study focused on the alga Chlorella variabilis RSM09, which was isolated from a brackish-water environment at Raksamae Bridge in Klaeng District, Rayong Province, Thailand. The effects of the carbon dioxide gas (CO2) concentration (0.03%, 10%, 20%, 30%, 40%, and 50% v/v), light intensity (3000, 5000, and 7000 Lux), and photoperiod (12:12, 18:6, and 24:0 h L/D) on algal growth and lipid production were investigated. The results indicated that C. variabilis RSM09 achieved optimal growth under 20% v/v CO2 aeration, with an optical density of approximately 2.91 ± 0.27, a biomass concentration of 1.32 ± 0.14 g/L, and a lipid content of 21.96 ± 0.29% (wt.). Among the three different light intensities, higher optical density (4.20 ± 0.14), biomass (1.79 ± 0.25 g/L), and lipid content (20.75 ± 2.0% wt.) were at the 5000 Lux of light intensity. Additionally, the photoperiod of 24:0 h (L/D) produced the highest biomass at 1.86 ± 0.21 g/L, followed by the 18:6 h light/dark photoperiod with a biomass of 1.65 ± 0.17 g/L, and the 12:12 h light/dark photoperiod with 1.35 ± 0.43 g/L. In contrast, the 18:6 h L/D photoperiod yielded a higher lipid concentration of 25.22 ± 2.06% (wt.) compared to the others. All cultured microalgae showed significant effects on fatty acid composition. Palmitic (16:0), linoleic (C18:2), and linolenic (C18:3) acids were predominant in C. variabilis RSM09 under all photoperiods. This study exhibited that the microalga C. variabilis RSM09 has great potential as a feedstock for biodiesel production.